Characterization of the sites and population dynamics of Aedes group (Diptera: Culicidae) in the oases of Biskra, Algeria (Journal of Biodiversity Conservation and Bioresource Management, 2022)
In this work, we studied the distribution and group dynamics of Aedes species in the region of Biskra, which were essentially formed by three species Aedes caspius, Aedes detritus, and Aedes dorsalis, as well as the physicochemical characteristics of their breeding sites. The results showed that Aedes caspius was most abundant in all the three sites surveyed, with a rate of 66.43% of the total fauna indicated. While the remaining two mosquito species have different rates during the study period. From the estimates of the main physicochemical parameters of the water, we were able to show the relationship between the abundance of these mosquito species and the typology of breeding sites. These mosquitos were present in alkaline sites, with medium mineralization and high oxygen levels. Thus, these species likely choose salty water environment.J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(1): 23-32